Presynaptic protein Synaptotagmin1 regulates the neuronal polarity and axon differentiation in cultured hippocampal neurons. Issue 1 (December 2015) - Inoue, Yuriko; Kamikubo, Yuji; Ezure, Hiromitsu; Ito, Junji; Kato, Yu; Moriyama, Hiroshi; Otsuka, Naruhito
Abstract Background Hippocampal neurons in the brain polarize to form multiple dendrites and one long axon. The formation of central synapses remains poorly understood. Although several of the intracellular proteins involved in the clustering of central neurotransmitter receptors and ion channels have been identified, the signals involved in pre- and postsynaptic differentiation remain elusive. Synaptotagmin1 is an abundant and important presynaptic vesicle protein that binds Ca2+ (J Biol Chem 277:7629–7632, 2002) in regulation of synaptic vesicle exocytosis at the synapse. Synapse consists of the formation of synaptic connections and requires precise coordination of Synaptotagmin1. It was reported Synaptotagmin1 plays an important roles in the formation of axonal filopodia and branches in chicken forebrain neurons (Dev Neurobiol 73:27–44, 2013). To determine if Synaptotagmin1 could have a role in formation of axon in hippocampal neurons, we investigated the effects of Synaptotagmin1 overexpression and knockdown using the shRNA on the growth and branching of the axons of primary hippocampal neurons. We showed that overexpression of Synaptotagmin1 leads to abnormal multiple axon formation in cultured rat hippocampal neurons. Results We first examined the effects of Synaptotagmin1 on the numbers of axon and dendrites. We found that the overexpression of Synaptotagmin1 led to the formation of multiple axons and induced an increase in the number of endogenous postsynaptic protein Homer1c clusters in cultured hippocampal neurons. Endogenous initial segment of axon was detected with anti-sodium channel (anti-NaCh) antibody and with anti-Tau1 (J Neurosci 24: 4605–4613, 2004). The endogenous initial segment of axon was stained with anti-NaCh antibodies and with anti-Tau1 antibodies. Then the numbers of prominence dyed positive were counted as axon. We attempted to specifically knockdown the endogenous Synaptotagmin1 with small hairpin RNAs (shRNAs). To further dissect the functions of endogenous Synaptotagmin1 in neuronal polarity, we used the shRNA of Synaptotagmin1 that specifically blocks the existence of endogenous Synaptotagmin1. When the shRNA of Synaptotagmin1 was introduced to the cells, the number of axons and dendrites did not change. Conclusions These results indicate that the accumulation of Synaptotagmin1 may play an important role in axon/dendrite differentiation.